Pedagogical Barriers of Teaching English Language at Kurdish Schools - Laveen Kamaran Muhamad; Samara Samir Jasim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This case study sheds the light on the pedagogical barriers that English language teachers encounter during the process of teaching English language; in addition to the most effective methods of teaching English language in middle schools in Erbil. The researchers investigate the obstacles that English language teachers face in the process of teaching English language along with the methods that are implemented by the English language teachers. For testing the hypothesis, a close-ended questionnaire was given to 20 English language teachers in middle schools in Erbil. The questionnaire aims at finding the barriers that English language teachers encounter, in addition to the most used method for teaching English language in the middle schools. The findings of the study illustrate that English language teachers experience serious problems in the process of teaching English language that prevent them from implementing the most effective teaching methods.